Essays of a lifetime - Fonseka, Carlo (2016)
Chiefly essays on science and religion; includes some essays on politics and government in Sri Lanka.
Keywords: Religion and science; Sri Lanka -- Politics and government; Socialisn; Politics; Human rights; Eduication